2016
DOI: 10.1155/2016/4513089
|View full text |Cite
|
Sign up to set email alerts
|

Mycoplasma genitalium: An Overlooked Sexually Transmitted Pathogen in Women?

Abstract: Mycoplasma genitalium is a facultative anaerobic organism and a recognized cause of nongonococcal urethritis in men. In women, M. genitalium has been associated with cervicitis, endometritis, pelvic inflammatory disease (PID), infertility, susceptibility to human immunodeficiency virus (HIV), and adverse birth outcomes, indicating a consistent relationship with female genital tract pathology. The global prevalence of M. genitalium among symptomatic and asymptomatic sexually active women ranges between 1 and 6.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 64 publications
2
39
0
2
Order By: Relevance
“…9 In women, MG infection has been associated with urethritis, cervicitis, pelvic inflammatory disease, susceptibility to HIV, adverse pregnancy outcomes and infertility. 10 Through intracellular localization 11 and antigenic variation, 12 MG could result in treatment-resistant chronic infection. 10 Molecular assays are currently employed, with high sensitivity, as the major diagnostic techniques for MG infection, although, at present they rely only on in-house protocols, as FDA-approved ones are not available.…”
Section: Introductionmentioning
confidence: 99%
“…9 In women, MG infection has been associated with urethritis, cervicitis, pelvic inflammatory disease, susceptibility to HIV, adverse pregnancy outcomes and infertility. 10 Through intracellular localization 11 and antigenic variation, 12 MG could result in treatment-resistant chronic infection. 10 Molecular assays are currently employed, with high sensitivity, as the major diagnostic techniques for MG infection, although, at present they rely only on in-house protocols, as FDA-approved ones are not available.…”
Section: Introductionmentioning
confidence: 99%
“…M. genitalium is a sexually transmissible micro‐organism distributed worldwide with a prevalence which varies depending on the country and population group being studied . In the general population, the prevalence of M. genitalium ranges from 1‐4% in males and 1–6% in females and can reach 38% in patients at high risk of STIs . In males, M. genitalium is a recognized cause of urethritis and represents approximately 15–20% of non‐gonococcal urethritis cases and approximately 30% of persistent or recurrent urethritis cases .…”
mentioning
confidence: 99%
“…Further, studies have demonstrated higher rates of Mgen antibodies in women with tubal factor infertility as compared to fertile women, suggesting a link between Mgen and female infertility. 36 A prospective United Kingdom study identified several risk factors including age younger than 21 years, black ethnicity, smoking, 2 or more sexual partners in the previous year, and concurrent infection with bacterial vaginosis. 37 A 2011 literature review (48 published reports worldwide) estimated Mgen prevalence at 7.3% in high-risk groups and 2.0% in lowrisk populations.…”
Section: Discussionmentioning
confidence: 99%